FINANCING THE RUSSIAN FEDERATION PROGRAM OF THE ELECTRIC POWER INDUSTRY DEVELOPMENT UNDER CONDITIONS OF FOREIGN POLICY AND ECONOMIC INSTABILITY - I. Ya. Lukasevich; N. V. Kuznetsov (Финансы: теория и практика)
The article discusses problems of financial support of power generating companies in the environment of the foreign policy and economic instability. The causes of low renewal rates in the power sector are exposed that threaten the implementation of the government program of its development.It is shown that the implementation of industry development projects requires a more effective government financial support along with the search of market financing tools.To solve the above problems, it is proposed to use non-government pension funds (NGPF) with simultaneous expansion of the list of their financial assets allowed for investment. Mechanisms of applying particular financial tools to financing the power companies are developed. Practical recommendations on how to make the program of the power industry development in the Russian Federation more effective are provided.